Biodewaterability and Liquid State Bioconversion of Activated Sludge Under Non-Sterilized Conditions - Sarkar, Md. Abdul Mannan (2006)
The study was conducted to evaluate the microbial treatment of domestic wastewater treatment plant (DWTP) or activated sludge by Liquid State Bioconversion (LSB) process under non-sterilized conditions. The selected two filamentous fungi, Penicillium corylophilum and Aspergillus niger isolated from Activated sludge were used to evaluate the treatment performance in LSB process under non-sterilized conditions through adaptation. It was observed that Penicillium corylophilum (WWZP1003) was the better strain compared to the Aspergillus niger (SCahmA103) for the bioconversion of activated sludge through adaptation. The visual observation in plate culture showed that about 95%-98% of cultured microbes (Penicillium corylophilum and Aspergillus niger) dominated in treated sludge after two days of treatment. In this study, it was also found that the Penicillium corylophil~rrn was capable of removing 94.40 % of chemical oxygen demand (COD) and 98.95% of turbidity of filtrate with minimum dose of inoculum of 10% V/V in activated sludge with total suspended solids (TSS) of 1% w/w. The pH level was lower at 3.4-3.5 (acidic condition) in the fungal treatment with maximum reduction of COD, turbidity and specific resistance to filtration (SRF) were observed. The results for SRF showed that the fungi led a great role to enhance the dewaterability and filterability. Ln particular, the strain Penicillium corylophilum had more capability (than Aspergillus niger) of reducing 93.20 % of SRF compared to the uninoculated sample. Effective results were observed by using fungal inoculum after 2 days of treatment. A statistical optimization of process factors was carried out to evaluate the linear and interaction effects on effective bioconversion of activated sludge using Penicillium. Three parameters namely temperature, agitation and pH with three levels were used to evaluate the process factors in term of biodegradability and biodewaterability/biofilterabiIity of activated sludge of 1% (w/w) TSS with 10% of inoculum dose of Penicillium corylophilum. A 3-level full factorial design (3" and response surface methodology (RSM) were used for the optimization of process factors through the biodegradability (removal of COD) and biodewaterability (SRF) of treatment sludge by a statistical software Minitab. The experimental data were designed by developing a second order polynomial regression model considering linear, quadratic and interaction effect. The optimum temperature, agitation and pH were observed to be 33S°C, 105 rpm and 5.5 respectively by the regression analysis on using experimental data under RSM. The maximum removal 98.5 % of COD, 99.0 % of turbidity and 95.0 % of SRF reduction were observed at that optimum process conditions in the activated sludge treatment by LSB under non-sterilized conditions. The maximum dry biosolids of 17.4 gkg production was observed with optimum process conditions by the fungal treatment (Penicillium corylophilum).The results in this study clearly indicate the effective bioconversion of activated sludge under non-sterilized conditions which may provide better waste management and disposd concerned.